2014
DOI: 10.1111/anu.12249
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fishmeal with biofloc meal in the diet of postlarvae of the Pacific white shrimpLitopenaeus vannamei

Abstract: This study evaluated the potential for the replacement of fishmeal (FM) by biofloc meal (BM) in the diet of Litopenaeus vannamei postlarvae. Four isonitrogenous (437.42 g kg À1 ) and isocaloric (19.84 kJ g À1 ) diets were formulated, in which FM was replaced with BM at 0% (T0), 7.5% (T7.5), 15% (T15) and 30% (T30). A commercial diet (CD) was used as reference. The study was conducted over 42 days in 50 L tanks connected to a water recirculation system. All tanks were stocked with three postlarvae (initial weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 45 publications
2
24
1
2
Order By: Relevance
“…Nevertheless, shrimp in the Control treatment exhibited higher growth performance during the feeding restriction phase. Although bioflocs are a source of several nutrients (Dantas et al, ; Ekasari et al, ), they were not enough to maintain weight gain during the fasting cycles in the present study. However, the fasting did not affect negatively shrimp survival and they probably used the biofloc in an attempt to meet their energy requirement for maintenance.…”
Section: Discussioncontrasting
confidence: 60%
“…Nevertheless, shrimp in the Control treatment exhibited higher growth performance during the feeding restriction phase. Although bioflocs are a source of several nutrients (Dantas et al, ; Ekasari et al, ), they were not enough to maintain weight gain during the fasting cycles in the present study. However, the fasting did not affect negatively shrimp survival and they probably used the biofloc in an attempt to meet their energy requirement for maintenance.…”
Section: Discussioncontrasting
confidence: 60%
“…Another important aspect to take into consideration is that the biofloc meal used in the present study was collected from a freshwater system containing tilapia, therefore the nutritional characteristics might be inferior to those in biofloc collected from shrimp farms. For example, Dantas, Valle, Brito, Calazans, Peixoto and Soares () recently reported that up to 30% of fish meal in diets for L. vannamei was successfully replaced by a biofloc meal collected from shrimp tanks.…”
Section: Discussionmentioning
confidence: 99%
“…; Dantas et al . ), although others processes have already been successfully replicated, upscaled and patented. Some of the final microbial products have been or will be specifically aimed at the animal nutrition sector and aquaculture industry (Glencross et al .…”
Section: A Look At the Bio‐economics Of Microbial Biomass Productionmentioning
confidence: 99%
“…Lee and Kim (2001) demonstrated that production costs of yeast Candida utilis could be significantly reduced (1.08-2.76 USD kg dry weight) by using molasses instead of complex media as nutrient substrate. Alternative methods for the production of yeasts and bacterial biomass using waste by-products derived from the food and agriculture industries are currently in experimental stage (Nouska et al 2015;Dantas et al 2016), although others processes have already been successfully replicated, upscaled and patented. Some of the final microbial products have been or will be specifically aimed at the animal nutrition sector and aquaculture industry (Glencross et al 2014;BFD 2015;WEF 2015).…”
Section: Reproductionmentioning
confidence: 99%